Análise econômica de investimentos que visam à produção de biogás e biofertilizante por meio de iodigestão anaeróbia na bovinocultura de corte - Montoro, Stela Basso [UNESP]; Santos, David Ferreira Lopes [UNESP]; Lucas Júnior, Jorge de [UNESP] (My University, 2013)
This study examines the feasibility of deploying digesters for treating waste from cattle at different scales considering under perspective economical. This is a descriptive exploratory research based on case study method on a rural property in the State of São Paulo. The techniques of DCF and Real Options were used for economic analysis. It was observed that the system of biogas and biofertilizer presents economic feasibility in feedlot cattle systems with more than 200 cattle using real options may be incorporated as a tool to assist in the expansion of the system, which increases the initial wealth owner. Thus, the results confirm the economic importance of this system of waste treatment that simultaneously preserves the environment, generates renewable energy and subsidizes inputs to the rural property

Este estudo analisa a viabilidade econômica da implantação de biodigestores para tratamento de resíduos da bovinocultura em diferentes escalas. Trata-se de uma pesquisa de natureza exploratória descritiva com base no método de estudo de caso numa propriedade rural no interior do Estado de São Paulo. As técnicas do Fluxo de Caixa Descontado e Opções Reais foram utilizadas para análise econômica. Observou-se que o sistema de biogás e biofertilizante apresenta viabilidade econômica em sistemas de confinamento bovino com mais de 200 cabeças de gado e que o uso das opções reais pode ser incorporado como instrumento para auxiliar no processo de expansão do sistema. Assim, os resultados comprovam importância econômica deste sistema de tratamento de resíduos que ao mesmo tempo preserva o ambiente, gera energia renovável e subsidia insumos à propriedade rural.
The economic analysis of investment aimed at biogas and fertilizer through anaerobic digestion in cattle management
Keywords: Analysis of economics; Options theory; Biodigester; Biomass energy; Cattle; Viabilidade econômica; Teoria de opções; Biodigestores; Energia de biomassa; Bovino corte